PENGARUH TINGKAT SUKU BUNGA DEPOSITO BERJANGKA TERHADAP PENINGKATAN JUMLAH NASABAH PADA BANK BRI CABANG MARISA KABUPATEN POHUWATO - Azis, Abdul (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
The interest level shows  a bank size, which a saving budget as a factor  to determine credibility performance. The aim of this research is analyzing whether the interest of money deposit period influence the improvement of the customers totality of BRI Bank of Marisa Pohuwato. Thais research used questionnaires to information related to the variable of this research. The sample of respondents is taken 37 person based on BRI Marisa Branch. The Analysis instrument used a simple regression. The result of this research shows that the level of the money interest of futures deposit is significantly positive influence towards the improvement of BRI Marisa Brach Customers  by calculating4.052 calculated > 2.120 ttable marks at the significant level  0.001 < 0.05.